Political Identity: Experimental Evidence on Anti-Americanism in Pakistan. Issue 5 (23rd September 2019) - Bursztyn, Leonardo; Callen, Michael; Ferman, Bruno; Gulzar, Saad; Hasanain, Ali; Yuchtman, Noam
Abstract: We identify Pakistani men's willingness to pay to preserve their anti-American identity using two experiments imposing clearly specified financial costs on anti-American expression, with minimal consequential or social considerations. In two distinct studies, one-quarter to one-third of subjects forgo payments from the U.S. government worth around one-fifth of a day's wage to avoid an identity-threatening choice: anonymously checking a box indicating gratitude toward the U.S. government. We find sensitivity to both payment size and anticipated social context: when subjects anticipate that rejection will be observable by others, rejection falls suggesting that, for some, social image can outweigh self-image.